Difusão da ciência moderna em instituições de ciência e tecnologia: um estudo de caso: o Museu Paraense Emílio Goeldi - Leite, Rose Aylce Oliveira (1990)
Considering its regional pecualiarities, and long period of existence, the Goeldi Museum is taken here as a subject to study the spread of modern science based on the model proposed by George Basalla. Through the analysis of administrative, technical, and historical data an attempt is made to reconstruct the steps for the incorporation and development of a scientific tradition at the Institution, and to identify a pattern by means of wich those steps can be detected at local, regional, and institutional contexts as proposed in the Basalla Model. The results from this research have showed that, in the Amazon Region in general, and in the Museum in particular, the development of the scientific activities is somewhat related to the Basalla Model, more precisely regarding its first two steps. However, autonomy and independence, the final stage predicted by the model, have not been achieved. We believe that this stage will be achieved only at the moment when technological and scientific issues can be adressed in a manner adequate to regional reality, and also ben discussed within a social perspective which permits us to aleborate a scientific policy corresponding to the needs of the majority of the population of Amazônia.